ENHANCING READING INSTRUCTION WITH RECIPROCAL TEACHING: A FOCUS ON TECHNOLOGY INTEGRATION - Kurniawan Arif Maspul (GLOBAL: Education Language and Humanity Journal, 2024)
The article highlights the importance of reciprocal teaching as a successful educational technique for improving reading abilities. Reciprocal teaching is an interactive strategy in which students act as instructors while using fundamental reading strategies like anticipating, clarifying, questioning, and summarizing. This adaptive strategy benefits students of all ages by improving essential reading abilities and comprehension skills; encourages active involvement, collaborative discussions, critical thinking, and interpretation, equipping students to confront complicated literary works and engage in intellectual debates. The study significantly supports the effectiveness of reciprocal instruction in enhancing reading comprehension, especially among struggling readers. Implementing reciprocal teaching requires a systematic method, with teachers gradually delegating responsibilities to students while modelling strategies. Integrating technology tools such as digital storytelling, virtual book clubs, and online collaboration platforms improves reciprocal teaching by adapting to different learning styles and keeping it relevant in the digital age. Educators who embrace reciprocal teaching can actively engage children, build critical thinking abilities, and instil a love of reading, ultimately contributing to a comprehensive and inclusive literacy program.